Bridging Worlds: How Islamic Civilization Shaped the Rise of Western Europe - Teddiansyah Nata Negara; Yusandi Yusandi; Wawan Hernawan; Ading Kusdiana (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
This article attempts to analyze the influence of Islamic civilization on the rise and progress of European-Christian (Western) civilization in the Middle Ages. The focus of this research is to trace the process of transferring knowledge (philosophy, science, technology, humanities, literature, medicine) from the Islamic world to European-Christian society through intellectual interaction in Andalusia (Spain), translation of scientific works of Islamic intellectuals, and through trade and the Crusades. This research employs a qualitative method with a literature study approach, where data are obtained from various academic literature sources and other scientific works. The results of the study show that Islamic civilization in Andalusia played a very decisive role in triggering intellectual development and European-Christian civilization which became the foundation for the Renaissance (Revival) in the West. Through a number of libraries and educational institutions in Andalusia and other Islamic centers, the process of translating books by Islamic scientists in Arabic into Latin took place by European-Christian students who brought them and spread them in their respective countries, thus giving birth to the spirit of the Renaissance in mainland Europe. This study concludes that Islamic civilization not only played a role as the guardian of the classical knowledge heritage of Greece, Rome, Persia, India, but also as a red carpet for European civilization, from the Dark Ages to the Renaissance (Revival).